Ethos and Argumentation in Speaker Roles: Judge, Minister, and Candidate - Garcia, Juliano dos Santos (2023)
In this study, the objective is to conduct a descriptive-interpretative analysis of argumentation and ethos constructed in light of the acknowledged change in social roles by an individual in their public life across three contexts: judge, minister of justice, and candidate. To achieve this, anchored in Textual Linguistics, we employ concepts and analytical procedures derived from the Theory of Argumentation in Discourse (TAD) for a textual/discursive analysis of the individual's personal publications on social media during the three indicated periods of social role transition. In terms of research, the primary inquiry revolves around how the generation and maintenance of a positive self-image or engagement in the transition/maintenance of positions were carried out. Results of the analyses indicate a particular shift in the speaker's employment of strategies for audience adherence in the analyzed composites since their assumption of a public office, particularly concerning the maintenance of the stereotyped ethos as a hero, initially created in the first phase as a judge.